2013
DOI: 10.1063/1.4818819
|View full text |Cite
|
Sign up to set email alerts
|

Influence of in-situ annealing ambient on p-type conduction in dual ion beam sputtered Sb-doped ZnO thin films

Abstract: Sb-doped ZnO (SZO) films were deposited on c-plane sapphire substrates by dual ion beam sputtering deposition system and subsequently annealed in-situ in vacuum and in various proportions of O2/(O2 + N2)% from 0% (N2) to 100% (O2). Hall measurements established all SZO films were p-type, as was also confirmed by typical diode-like rectifying current-voltage characteristics from p-ZnO/n-ZnO homojunction. SZO films annealed in O2 ambient exhibited higher hole concentration as compared with films annealed in vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…The thermal activation energy for Sb acceptor was found to be 115 ± 5 meV, close to the theoretical prediction [56]. A similar acceptor-like Sb Zn -2V Zn complex formation was observed for Sb-doped ZnO (SZO) thin films fabricated by dual ion beam sputtering technique [106]. The SZO films exhibited hole concentration, mobility, and resistivity values of 1.356 × 10 17 cm −3 , 6.737 cm 2 /V s, and 6.842 Ω-cm, respectively.…”
Section: Antimony Dopingsupporting
confidence: 74%
“…The thermal activation energy for Sb acceptor was found to be 115 ± 5 meV, close to the theoretical prediction [56]. A similar acceptor-like Sb Zn -2V Zn complex formation was observed for Sb-doped ZnO (SZO) thin films fabricated by dual ion beam sputtering technique [106]. The SZO films exhibited hole concentration, mobility, and resistivity values of 1.356 × 10 17 cm −3 , 6.737 cm 2 /V s, and 6.842 Ω-cm, respectively.…”
Section: Antimony Dopingsupporting
confidence: 74%
“…As reported by previous study, 24 rather than Zn or itself and the Sb-O bond has been proven to be present in the Sb-doped ZnO. 25 Therefore, the increase in the Sb valence state implies that more O ions are bound to the doped Sb ions than to Zn ions in the ZnO lattice.…”
mentioning
confidence: 80%
“…The XPS study on the chemical state of Sb in the ZnO:Sb (2%) samples upon different annealing temperatures showed that the Sb 5þ /Sb 3þ ratio in the samples anti-correlates with the electron concentration and correlates with the V Zn -Sb acceptor complex concentration. Pandey et al 33 carried out the XPS study on Sb-doped ZnO fabricated by dual ion beam sputtering and a high Sb 5þ /Sb 3þ ratio was correlated with the hole concentration, and thus the Sb Zn -2V Zn shallow acceptor. This result is consistent with the assignment of the V Zn -Sb acceptor complex to Sb Zn -2V Zn , rather than Sb i -3V Zn as Sb i -3V Zn is a deep acceptor.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 12(a)-12(c), respectively, show the XPS spectra of the Sb 3d 3/2 state of the as-grown ZnO:Sb (2%) sample and those upon annealing at 750 and 900 C. The 3d 3/2 peaks were fitted by the Sb 3þ and Sb 5þ peaks locating at $540.2 eV and 540.8 eV, respectively. 33 The fitted intensity ratios of the peaks Sb 5þ /Sb 3þ are 1.61, 4.82, and 2.33 for the as-grown, 750, and 900 C annealed ZnO:Sb samples, respectively. The maximum Sb 5þ /Sb 3þ intensity ratio at the annealing temperature of 750 C well anti-correlates with the minimum of the electron concentration (see Fig.…”
Section: Xps Studymentioning
confidence: 93%